Pengaruh Persepsi Manfaat dan Persepsi Risiko Terhadap Keputusan Pembelian Tiket Pesawat Menggunakan Paylater oleh Generasi Z - Rivaldo Adam Gustiarto; Adipura Danang Maulana (Ikatan Da'i Indonesia, 2025)
Using the Generation Z Paylater feature in the Special Region of Yogyakarta, this study investigates the influence of perceived benefits and perceived risks on airplane ticket purchase decisions. The rapid growth of digital technology and e-commerce, especially in technology-based financial services (financial technology), is driving consumer behavior to become more practical, including buying airline tickets. Young people, especially Gen Z, are starting to use paylater, which allows customers to pay as they buy and pay at a later date. The research method used is a quantitative method with a survey method through distributing questionnaires to 100 respondents who are Generation Z students who live or study in the Special Region of Yogyakarta. The sampling technique used purposive sampling. The data obtained were analyzed using validity, reliability, classical assumptions, multiple linear regression, and hypothesis testing (t test and F test) with the help of SPSS software. The results showed that perceived benefits have a positive and significant effect on the decision to purchase airplane tickets using Paylater. Perceptions of risk also show a positive and significant influence, although in some indicators such as psychological and social risks, the influence is less dominant than financial and performance risks. Simultaneously, the two independent variables, namely perceived benefits and perceived risks, have a significant effect on purchasing decisions. The coefficient of determination (R²) of 0.520 indicates that 52% of the variation in purchasing decisions can be explained by these two variables, while the rest is influenced by other factors outside the research model.